Pengaruh Media Pendidikan Gizi (Komik) terhadap Peningkatan Pengetahuan dan Perubahan Berat Badan pada Anak Sekolah Dasar dengan Obesitas - Arie Nugroho (Politeknik Kesehatan Tanjung Karang, 2018)
School age is a time when children experience rapid growth. At this age of physical activity continues to increase such as play, exercise. Wrong eating habits in schoolchildren can lead to serious nutritional problems, such as obesity. Eating behavior such as consumption of junk food and fried is associated with the occurrence of obesity in school children. This study was to determine the effect of nutritional education media (comic) to increase knowledge and weight loss in elementary school children with obesity in the city of Bandar Lampung. This study included experiment research with quasi-experiment design study, conducted in Bandar Lampung City Elementary School. Subjects in the case were obese primary school children who received nutritional media (comic) intervention. The number of subjects consisted of 31 cases and 31 controls. The variables observed included weight changes and changes in knowledge of data. Data analysis was done by independent t-test and pair t-test. There was the influence of nutrition media intervention (comic) to the score of knowledge was shown with p-value=0,001. Where the increase of knowledge score only in the treatment group that was from 10,96+1,99 to 13,38+1,68. While nutrition media intervention (comic) did not give effect to changes in obese child weight shown with a p-value that is 0,491 for treatment group and 0,725 for the control group. The nutritional media (comic) interventions can improve the knowledge score of obese primary school children but have no effect on changes in child weight. The intervention should be done more than 2 weeks to see directly effect of nutritional media (comic) intervention on weight change, we should involve the professional in making comics and experiment on the use of comics as a material of intervention to the same population.